Methodical Recommendation for the Use of Information Technology in Primary Classes - Bayramberdiyev Nurnazar Bagibek ogli (Indonesian Journal of Innovation Studies, 2022)
This article provides information on the importance of using information technology in primary classes. It is known that primary education is the foundation of the educational system, the quality of teaching students will depend on it, and this will be a great responsibility on the part of the primary school teacher. For a long time in the educational system, the primary school was considered a "school of skills", that is, the stage of education in which the student must master such basic skills as reading, writing, and counting for further education.